A TR(i)P to Cell Migration: New Roles of TRP Channels in Mechanotransduction and Cancer - Canales, Jimena; Morales, Diego; Blanco, Constanza; Rivas, José; Díaz, Nicolás; Angelopoulos, Ioannis; Cerda, Oscar (Frontiers in Physiology, 2019)
Cell migration is a key process in cancer metastasis, allowing malignant cells to spread from the primary tumor to distant organs. At the molecular level, migration is the result of several coordinated events involving mechanical forces and cellular signaling, where the second messenger Ca2+ plays a pivotal role. Therefore, elucidating the regulation of intracellular Ca2+ levels is key for a complete understanding of the mechanisms controlling cellular migration. In this regard, understanding the function of Transient Receptor Potential (TRP) channels, which are fundamental determinants of Ca2+ signaling, is critical to uncovering mechanisms of mechanotransduction during cell migration and, consequently, in pathologies closely linked to it, such as cancer. Here we review recent studies on the association between TRP channels and migration-related mechanotransduction events, as well as in the involvement of TRP channels in the migration-dependent pathophysiological process of metastasis.